PROBLEMS OF TRAINING OF QUALIFIED STAFF FOR SPACE INDUSTRY - Vladimir N. Zimin; Boris V. Padalkin (Высшее образование в России)
The article focuses on the special features of integrated continuing target training of personnel for space industry. It is shown that support of young people and schoolchildren researches and introduction of space themes in the courses of technical and engineering disciplines ensures the quality of training highly skilled staff for space industry. The article shows the role the Youth Cosmic Centre in involving students in scientific and technical creativity.